Development of phenomenon-based learning components through community services learning (SULAM) course addressing substance use disorders: experiences before and during COVID-19 pandemic. - Mohd Taufek, Nor Hidayah (2021)
Development of in-depth learning among university students can be generated from experiencing real world phenomena through community services and engagement. The unique experiences gained from community services activities from before and during COVID-19 pandemic has permitted pharmacy students to address population with substance use disorders through different methods. This paper aimed to report the experiences from community services activities by pharmacy students before and during the pandemic with development in components of phenomenon-based learning. The different nature of activities conducted before and during the pandemic have addressed experiential learning values based on the adaptation to the changed phenomenon. Although the experiential learning outcomes were not assessed or measured in SULAM activities, students’ reflections have demonstrated learning values to be part of phenomenon-based learning. These include 1) team-based learning 2) application of knowledge for innovation 3) metacognitive awareness and 4) transdisciplinary, as part of experiential learning reflections. Future studies are needed to explore the potential application phenomenon-based learning to be implemented in SULAM course to improve experiential learning performance in Malaysia.